Challenges faced by nurses in using pain assessment scale in patients unable to communicate: a qualitative study - Kolsoum Deldar; Razieh Froutan; Abbas Ebadi (BMC, 2018)
Abstract Background One helpful strategy adopted for pain management in non-verbal, intubated patients is the use of a proper pain assessment scale. The purpose of the present study is to achieve a better and deeper understanding of the existing nurses' challenges in using pain assessment scales among patients unable to communicate. Methods This qualitative study was conducted using content analysis. Purposive sampling was used to select the participants and continued until data saturation. The participants included 20 nurses working in intensive care units. Data was collected using semi-structured interviews and analysis was done using an inductive approach. Results Four categories and ten sub-categories were extracted from the experiences of the nurses working in the intensive care units in terms of nursing challenges in using non-verbal pain assessment scales. The four categories included "forgotten priority", "organizational barriers", "attitudinal barriers", and "barriers to knowledge". Conclusions The findings of the present study have shown that various factors might influence on the use of non-verbal pain assessment scales in patients unable to communicate. Identifying these challenges for nurses can help take effective steps such as empowering nurses in the use of non-verbal pain assessment scales, relieving pain, and improving the quality of care services.